Influence of Duplex USSP/Nitriding Surface Treatments on the Dry Sliding Behavior of Ti6Al4 V/AISI 316L Tribopairs. (2015) - Maire, L.; Faure, L.; Philippon, S.; Novelli, M.; Marcos, G.; Czerwiec, T.; Grosdidier, T.
Abstract: This contribution gives the first results of an ongoing research aiming at determining the effect of duplex USSP/Nitriding surface treatments on the dry sliding behavior of an AISI 316L steel against a Ti6Al4 V counterpart under quasi-static and dynamic conditions. While the nitriding process, carried out solely, leads to a 8 μm thick layer of hard (850 HV) expanded austenite, the effect of the additional USSP pretreatment is also to harden the sub-surface over about 300 μm and raise the hardness of the top surface to about 1200 HV. After a quasi-static friction test against the fairly soft Ti6Al4 V, the 8 μm thick nitrided layer was not worn but was significantly modified. A 1 μm thick layer of heavily plastically deformed material was observed at the top surface within which some transverse cracks formed and could sometimes extend throughout the entire nitrided layer. Comparatively, after a dynamic friction test, some additional recrystallization took place in the sub-surface of the USSP + nitrided treated 316L steel at the sliding output located at the end of the pads; indicating thereby that the temperature could reach values above 600 °C during friction.